Improving Energy Decisions: Towards Better Scientific Policy Advice for a Safe and Secure Future Energy System - Droste-Franke, B (Springer, 2015)
Managing a successful transition of the current energy supply system to less carbon emitting options, ensuring a safe and secure supply during the whole process and in the long term, is one of the largest challenges of our time. Various approaches and first implementations show that it is not only technological issue, but also a matter of societal acceptance and acceptability, considering basic ethic values of the society.